Intimate Partner Violence and Rural Public Health Nursing Practice: Challenges and Opportunities - Tracy A. Evanson (Rural Nurse Organization; Binghamton University, 2006)
Health care providers of all disciplines encounter victims of intimate partner violence (IPV) in all practice settings. However, few studies have examined the role of public health nurses (PHNs) who visit the homes of families where IPV is occurring, and none have focused on the unique aspects of rural PHN practice with these families. This research, derived from a larger descriptive phenomenology study, describes the unique challenges and opportunities experienced by rural home-visiting PHNs when working with families where IPV was occurring. The rural PHNs described unique opportunities in their abilities to establish and maintain relationships with families, to assess for IPV, to advocate for victims with other community providers, and to keep perspective about their work. However, living and practicing in rural areas also created unique challenges related to barriers to disclosure of IPV, maintaining confidentiality, helping victims access resources, getting support for themselves, and establishing and maintaining professional-personal boundaries.